2006
DOI: 10.1002/pssa.200521349
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray powder diffraction study of the Cu2Cd1–xMnxSnSe4 alloys

Abstract: The alloys of the Cu 2 CdSnSe 4 -Cu 2 MnSnSe 4 system were investigated using the X-ray powder method that showed the continuous solubility of the original system components at 670 K. The refinement of the crystal structures of Cu 2 MnSnSe 4 (space group (SG) I4 2m, a = 0.57362(4) nm, c = 1.14007(7) nm, c/a = 1.9875, R I = 0.0531, R P = 0.1186) and of the solid solution of Cu 2 Cd 0.5 Mn 0.5 SnSe 4 composition (SG I4 2m, a = 0.57935(2) nm, c = 1.14036(5) nm, c/a = 1.9683, R I = 0.0455, R P = 0.0902) was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 24 publications
(10 reference statements)
8
25
0
Order By: Relevance
“…In recent works, lattice parameter values and phase diagrams for the Cu 2 Cd 1−z Mn z GeSe 4 , Cu 2 Cd 1−z Fe z GeSe 4 and Cu 2 Zn 1−z Fe z GeSe 4 alloy systems have been studied [6,7]. The X-ray powder diffraction study of the Cu 2 Cd 1−z Mn z SnSe 4 alloys has been given by Sachanyuk et al [8], but information on the phase diagram for this system has not as yet been reported.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In recent works, lattice parameter values and phase diagrams for the Cu 2 Cd 1−z Mn z GeSe 4 , Cu 2 Cd 1−z Fe z GeSe 4 and Cu 2 Zn 1−z Fe z GeSe 4 alloy systems have been studied [6,7]. The X-ray powder diffraction study of the Cu 2 Cd 1−z Mn z SnSe 4 alloys has been given by Sachanyuk et al [8], but information on the phase diagram for this system has not as yet been reported.…”
Section: Introductionmentioning
confidence: 98%
“…1. The crystal structure of these compounds has been given in earlier works [4,5,[8][9][10][11][12], and it has been found that all of them have the stannite tetragonal structure (I42m), with unit cell parameter values a = 5.8337(2) Å, c = 11.4039(4) Å for the Cu 2 CdSnSe 4 [10], a = 5.694(2) Å, c = 11.286(4) Å for the Cu 2 FeSnSe 4 compound [12] and a = 5.7362(4) Å, c = 11.4007(7) Å for the Cu 2 MnSnSe 4 [8]. Matsushita et al [13] reported that Cu 2 CdSnSe 4 has a congruent type of melting at 1053 K (780 • C), while according to Olekseyuk and Piskach [10,14] it is formed incongruently at 1055 K (782 • C).…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray powder diffraction study of the Cu 2 Cd 1−z Mn z SnSe 4 system has been reported in Ref. [12].…”
Section: Introductionmentioning
confidence: 99%
“…Internal atomic coordinates are optimized starting from experimental data of Cu 2 MnSnS 4 [10] and Cu 2 MnSnSe 4 . [16] The 2×4×1 Monkhost-Pack k-point grid in the Brillouin zone is used. [17] Cu-3d4s, Mn-3d4s, Sn-5s5p, S-3s3p, and Se-4s4p electrons are treated as valence states.…”
Section: Methodology and Structural Detailsmentioning
confidence: 99%
“…Lattice constants are fixed to the experimental data: a = b = 5.514Å, c = 10.789Å for Cu 2 MnSnS 4 [10] and a = b = 5.736Å, c = 11.401Å for Cu 2 MnSnSe 4 [16] in the tetragonal I42m structure. In order to impose the experimentally observed AFM spin configuration in Cu 2 MnSnS 4 [10] with the propagation vector k = ( (c)) (note that, to our knowledge, the experimental magnetic configuration for Cu 2 MnSnSe 4 has not been reported yet).…”
Section: Methodology and Structural Detailsmentioning
confidence: 99%